Features of impact of hyperferritinemia in combination with hyperuricemia on the course of gout. - G. P. Kuzmina; O. M. Lazarenko (Medičnì Perspektivi)
The purpose of the study is to find out the frequency of development of hyperferritinemia in combination with hyperuricemia in patients with gout, to assess their pathogenetic significance and to outline their role in the development of joint syndrome, to identify informative prognostic criteria. 72 patients with gout were examined. The 1st (main) group included 37 patients with gout with hyperuricemia combined with hyperferritinemia, whose mean age (SD) was 55.9 (10.7) years. Group 2 (comparison group) included 35 patients with gout and hyperuricemia and normal levels of ferritin (mean age - 52.8 (4.8) years). Group 3 (control) group included 20 practically healthy individuals (mean age 52.0 (2.9) years). The average level of blood uric acid was significantly different (p=0.0254) in the main group and the comparison group and amounted to 464.5 (122.5) μmol/L and 403.8 (403.8; 403.8), respectively. The value of ferritin in the main group was significantly higher 410.2 (356.2; 415.2), p<0.01) ng/mL, than in the comparison group (132.1 (20.5) ng/mL, as well as the values of the urine uric acid and C-reactive protein values (hs-CRP) (p=0.0001) 8.2 (6.0; 8.2) and 5.8 (6.1) mg/L, respectively. A direct reliable correlation was established (r=0.30; p<0.05) between the level of blood uric acid and ferritin, the duration of gout (r=0.41; p<0.05), the total number of affected joints (r=0.35; p<0.03), the severity of gout (r=0.36; p<0.05), as well as between the level of ferritin and the number of exacerbations of gout (r=0.44; p<0.05). Hyperferritinemia in combination with hyperuricemia is found in 51.0% of patients with gout, significantly worsening the course of the inflammatory process Patients with gout and high levels of ferritin, unlike patients with normal levels of ferritin, have the following clinical anamnestic signs: greater number of exacerbations of gout per year, duration of gout and last outbreak of gout, exacerbation of arthritis, total number of affected joints, pain intensity during exacerbation by scale VAS. In patients with gout, the severity of the course and the form of gouty arthritis, which are determined according to imaging methods (erosion, peripheral and bone tophus, the sign of "double contour", the degree of narrowing of the joint gaps and the severity of subchondral sclerosis), have prognostic significance. The association of ferritin with blood uric acid in gout does not depend on the level of hs-CRP.